Patient-centred care, health behaviours and cardiovascular risk factor levels in people with recently diagnosed type 2 diabetes: 5-year follow-up of the ADDITION-Plus trial cohort - Dambha-Miller, Hajira (BMJ Open, 2016)
OBJECTIVE: To examine the association between the experience of patient-centred care (PCC), health behaviours and cardiovascular disease (CVD) risk factor levels among people with type 2 diabetes. DESIGN: Population-based prospective cohort study. SETTING: 34 general practices in East Anglia, UK, delivering organised diabetes care. PARTICIPANTS: 478 patients recently diagnosed with type 2 diabetes aged between 40 and 69 years enrolled in the ADDITION-Plus trial. MAIN OUTCOME MEASURES: Self-reported and objectively measured health behaviours (diet, physical activity, smoking status), CVD risk factor levels (blood pressure, lipid levels, glycated haemoglobin, body mass index, waist circumference) and modelled 10-year CVD risk. RESULTS: Better experiences of PCC early in the course of living with diabetes were not associated with meaningful differences in self-reported physical activity levels including total activity energy expenditure (β-coefficient: 0.080 MET h/day (95% CI 0.017 to 0.143; p=0.01)), moderate-to-vigorous physical activity (β-coefficient: 5.328 min/day (95% CI 0.796 to 9.859; p=0.01)) and reduced sedentary time (β-coefficient: −1.633 min/day (95% CI −2.897 to −0.368; p=0.01)). PCC was not associated with clinically meaningful differences in levels of high-density lipoprotein cholesterol (β-coefficient: 0.002 mmol/L (95% CI 0.001 to 0.004; p=0.03)), systolic blood pressure (β-coefficient: −0.561 mm Hg (95% CI −0.653 to −0.468; p=0.01)) or diastolic blood pressure (β-coefficient: −0.565 mm Hg (95% CI −0.654 to −0.476; p=0.01)). Over an extended follow-up of 5 years, we observed no clear evidence that PCC was associated with self-reported, clinical or biochemical outcomes, except for waist circumference (β-coefficient: 0.085 cm (95% CI 0.015 to 0.155; p=0.02)). CONCLUSIONS: We found little evidence that experience of PCC early in the course of diabetes was associated with clinically important changes in health-related behaviours or CVD risk factors. TRIAL REGISTRATION NUMBER: ISRCTN99175498; Post-results.